2021
DOI: 10.1007/s10943-021-01233-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Spiritual Quality of Life during the COVID-19 Pandemic: A Multivariate Analysis

Abstract: COVID-19 has led to the implementation of various social and sanitary measures, impacting populations' quality of life. Aims: Documenting the spiritual quality of life (SQoL) of university employees and students in Quebec, Canada. A survey of 2,202 employees and students was conducted using health measurement tools, including the short version of the WHOQoL-SRPB. We ran a multiple linear regression to determine which variables promote the SQoL. SQoL was very low (2.92/5). Positive mental health, religion, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…For example, Koenig ( 2020 ) emphasised the role of religious faith and practice in maintaining good health during the outbreak. Similarly, Cadell et al ( 2021 ) showed that even in secular cultures, spirituality has played an active and positive role in the quality of life and health during the COVID-19 pandemic. Also, Ferrell et al ( 2020 ) stressed that the COVID-19 has revealed an urgent need for spiritual care as an integral part of whole-person palliation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Koenig ( 2020 ) emphasised the role of religious faith and practice in maintaining good health during the outbreak. Similarly, Cadell et al ( 2021 ) showed that even in secular cultures, spirituality has played an active and positive role in the quality of life and health during the COVID-19 pandemic. Also, Ferrell et al ( 2020 ) stressed that the COVID-19 has revealed an urgent need for spiritual care as an integral part of whole-person palliation.…”
Section: Discussionmentioning
confidence: 96%
“…This is important because although the COVID-19 pandemic has brought spiritual care to the forefront of healthcare and there is growing evidence for the positive role of SCP in the healthcare system during the current healthcare crisis (Busfield, 2020 ; Cadell et al, 2021 ; Drummond & Carey, 2020 ; Dutra & Rocha, 2021 ; Ferrell et al, 2020 ; Harrison & Scarle, 2020 ; Jones et al, 2020 ; Koenig, 2020 ; Murphy, 2020 ; Papadopoulos et al, 2021 ; Peacock, 2020 ; Sarmiento, 2020 ; Swift, 2020 ; Weinberger-Litman et al, 2020 ; Wierstra et al, 2020 ), little is known about the impact of COVID-19 on spiritual care in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be considered that culture and belief systems are important in an international setting. In a study involving university students in Canada, it was determined that spirituality played a positive role in quality of life and health during the COVID-19 pandemic (Cherblanc et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…"The World Health Organization Quality of Life" (1995) explains the quality of life as an individual's perception of life positioning. It includes spiritual and psychological aspects of health which encompasses the positive assessment a person makes relative to his spiritual and psychological well-being (Cherblanc et al, 2021), making both constructs intertwined. Spiritual well-being could be seen as one kind of healthy psychological manifestation of the tendency to focus on the things that lie outside of oneself (Paloutzian et al, 2012), where psychosocial and a more religious dimension becomes a unifying force to integrate health's physical, emotional and social dimensions (Coppola et al, 2021).…”
Section: Relationship Between Psychological and Spiritual Well-beingmentioning
confidence: 99%